Evaluation of Sunscreen Protection Factor Values (SPF) for some Aromatic Acids and their Salts of Mono- and Bivalent Metals by UV Spectrophotometer - Mosa, Fathia A.; Milad, Aisha; Agailm, Marwa A.; Hadia, Rem A.; Khalil, Hana H. (Scientific Journal for Faculty of Science-Sirte University, 2023)
This study aimed to determine the ultraviolet absorption for some carboxylic acids and their salts of mono- and bivalent metals as organic UV filters by UV spectrophotometer, as well as, calculate the values of the sun protection factor (SPF) for these compounds. The solutions of organic UV filters are subjected to absorbance measurements in the range of 290 to 320 nm, with five nm intervals, using the ultraviolet spectrometer. The experiments have been carried out in three different solvents: H2O, MeOH, and EtOH. These salts included sodium benzoate, sodium salicylate, calcium benzoate, and calcium salicylate. The calculated sun protection factor (SPF) of these solutions was evaluated using the Mansur equation. All organic filters showed some sunlight protection properties. The best-calculated SPF values were 47.0 for salicylic acid, followed by the sodium salicylate salt at 40.3 and then the calcium salicylate salt at 39.7. These salicylic acid salts showed a high ability of UV absorbance compared to benzoic acid salts which showed SPF values of 11.5. This study presented organic UV filters with high SPF values and high solubility in polar solvents such as water and ethanol. Sodium and calcium salicylates would be recommended for use in the manufacture of sunscreen formulations.